2020
DOI: 10.7150/jca.40744
|View full text |Cite
|
Sign up to set email alerts
|

A thioredoxin reductase inhibitor ethaselen induces growth inhibition and apoptosis in gastric cancer

Abstract: Gastric cancer (GC) is the third leading cause of cancer deaths worldwide. Conventional chemotherapy has been proven useful to only a portion of the patients. Previous developed targeted drugs are more effective and tolerable than conventional drugs. Thus the development of novel drugs targeting markers is an urgent task and the main direction for future research. Ethaselen, an inhibitor of thioredoxin reductase (TrxR), has been considered an important anticancer target drug. Previous studies show that it is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…We have successfully established and passaged GC-PDO, and verified the consistency of these organs with the primary carcinoma tissue through histopathological examination [ 31 ]. Our previous study has suggested that BBSKE induced growth inhibition and apoptosis in gastric cancer cells and GC Patient-Derived organoid [ 32 ]. In the present study, we investigated whether BBSKE could synergize to enhance the anti-tumor effects of oxaliplatin in gastric cancer cells and GC-PDO.…”
Section: Introductionmentioning
confidence: 99%
“…We have successfully established and passaged GC-PDO, and verified the consistency of these organs with the primary carcinoma tissue through histopathological examination [ 31 ]. Our previous study has suggested that BBSKE induced growth inhibition and apoptosis in gastric cancer cells and GC Patient-Derived organoid [ 32 ]. In the present study, we investigated whether BBSKE could synergize to enhance the anti-tumor effects of oxaliplatin in gastric cancer cells and GC-PDO.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that upon oxidative stress, cysteine thiol groups in Trx may be oxidatively modified which results in protein inactivation [55,56]. Moreover, it was reported that Trx is expressed in proliferating cells and downregulated in apoptotic ones [57]. Our results have also shown that survivin level decreases in MOLM-14 cells after combined treatment.…”
Section: Discussionsupporting
confidence: 65%
“…The IC 50 value of GC376 has been reported as 26.4 ± 1.1 nM against SARS-CoV-2 M pro ( 43 ). However, another study demonstrated that 49 possesses significant IC 50 values and inhibits the growth of several cancer cells ( 123 ). Therefore, further biological investigations may improve our understanding of the inhibitory properties of 49 against SARS-CoV-2 M pro.…”
Section: Discussionmentioning
confidence: 99%